Does Diversification Protect Bank Lending Against Uncertainty? - Van Dan Dang; Hoang Chung Nguyen (Credit and Capital Markets – Kredit und Kapital, 2022)
The paper examines whether bank diversification in multiple dimensions can protect bank lending from uncertainty shocks. We use a panel of Vietnamese commercial banks during 2007?–?2019 for empirical analysis and measure uncertainty in banking by the dispersion of bank-level shocks. Our results confirm that banks may reduce loan growth and experience more credit risk amid greater uncertainty. These adverse impacts of uncertainty on bank lending (both quantity and quality) are significantly alleviated by bank diversification in the loan portfolio, income, and funding aspects. Our findings offer practical implications for regulators and banks themselves: bank diversification can effectively act as a lending shock absorber in periods of high uncertainty.
Keywords: D81; E50; G21; G32; 330; Bank lending; Credit risk; Diversification; Uncertainty